SISTEM INFORMASI LAYANAN SERVIS PADA BENGKEL MOBIL BERKAH JAYA BERBASIS WEB - Aripin, Ahmad Jaenal; Febrina, Febrina; Putra, Stefan Setiadi Dwitama; Hidayat, Hidayat (Journal of Computer Science and Technology (JCS-TECH), 2025)
The advancement of information technology has driven digital transformation across various sectors, including automotive workshop services. Bengkel Berkah Jaya still operates using manual business processes, leading to inefficiencies, recording errors, and limited customer service. This study aims to develop a web-based automotive service information system to automate service processes, simplify information access, and improve operational efficiency and customer satisfaction. The system development was carried out using the Waterfall method through several stages: needs analysis, system design using UML, implementation with Laravel and MySQL, testing, deployment, and maintenance. The research results show that all functions in the service information system have operated properly. Evaluation through questionnaires indicates an average user satisfaction level of 84% regarding system features and ease of use. Most respondents stated that the application is easy to use and helpful in supporting service processes. However, the visual design aspect still needs improvement. Overall, the system provides an effective solution for enhancing service quality and workshop operations. The application is expected to help Bengkel Berkah Jaya expand its reach and become more responsive to customer needs.